Prevalence and correlators of burnout among health professionals during different stages of the COVID-19 pandemic in China - Qin, Zhengshan; He, Zhehao; Yang, Qinglin; Meng, Zeyu; Lei, Qiuhui; Wen, Jing; Shi, Xiuquan; Liu, Jun; Wang, Zhizhong (Frontiers in Psychiatry, 2023)
Background: Persistently increased workload and stress occurred on health professionals (HPs) during the COVID-19 pandemic in the past 3years. This study aimed to explore the prevalence and correlators of burnout among Chinese HPs during different stages of the pandemic. Methods: Three repeated online cross-sectional studies conducted in different stages of the COVID-19 pandemic, wave1: after the first peak of the pandemic, wave2: the early period of zero-COVID policy, wave3: the second peak of the pandemic happened in China. Two dimensions of burnout: emotional exhaustion (EE) and declined personal accomplishment (DPA) were assessed using Human Services Survey for Medical Personnel (MBI‐HSMP), a 9-item Patient Health Questionnaire (PHQ-9), and 7-item Generalized Anxiety Disorder (GAD-7) to assess the mental health condition. Results: The overall prevalence of EE and DPA were 44.6% and 36.5%, respectively, while the highest prevalence of EE and DPA was found in the first wave (44.6% and 36.5%), then the second wave (44.9% and 34.0%), and the third wave had the lowest prevalence of 42.3% and 32.2%. Logistic regression model identified that depression and anxiety were persistently correlated with a higher prevalence risk of both EE and DPA. While Females (wave 1: OR=1.19, 95%CI: 1.00~1.42; wave 3: OR =1.20, 95%CI:1.01~1.44), living in the middle area (wave 2: OR=1.66, 95%CI: 1.20~2.31) and west area (wave 2: OR=1.54, 95%CI: 1.26~1.87) had a higher prevalence risk of EE, in contrast, those who age over 50 years (wave 1: OR=0.61, 95%CI: 0.39~0.96; wave 3: OR=0.60, 95%CI: 0.38~0.95), provide care to patients with COVID-19 (wave 2: OR=0.73, 95%CI: 0.57~0.92) had a lower risk of EE. Working in the psychiatry section (wave 1: OR=1.38, 95%CI: 1.01~1.89) and being minorities (wave 2: OR=1.28, 95%CI: 1.04~1.58) had a higher risk of DPA, while aged over 50 years had a lower risk of DPA (wave 3: OR=0.56, 95%CI: 0.36~0.88). Conclusion: This three-wave cross-sectional study revealed the prevalence of burnout among health professionals at a high level persistently during the three different stages of the pandemic. Suggesting that inadequate resource of functional impairment prevention for health professionals and sustained monitoring of these variable worth noting.